EDUCATION ON THE EMERGENCY RESPONSE SYSTEM AS AN EFFORT TO HANDLE FIRE DISASTERS IN ISLAMIC BOARDING SCHOOLS - Ratriwardhani, Ratna Ayu; Sahri, Moch.; Sunaryo, Merry; Nurmianto, Eko; Taqiyaa, Nirmala Kaana (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2024)
Islamic boarding schools are one of the educational institutions that have a risk of danger, because in their activities they always use tools and materials to support the teaching and learning process and energy sources that can cause danger. Energy sources such as electricity, LPG gas and chemicals, if not properly managed, can pose a risk of fire. Fire is the most frequently encountered disaster and can be classified as a natural disaster or a disaster caused by human actions. The danger of fire can occur at any time and at any time, resulting in a lot of material, environmental, financial, equipment and human losses. Based on a survey conducted at the location, the knowledge and skills regarding handling emergency conditions, especially fires, have not been mastered by Islamic boarding school administrators and students. The aim of this community service activity is to overcome the fire disaster at the Assalafi Al-Fithrah Islamic Boarding School in Surabaya. The solution provided is to provide disaster mitigation material to Islamic boarding school administrators and students in the Assalafi Al-Fithrah Islamic Boarding School environment in Surabaya and fire prevention training using a light fire extinguisher. The activity was held on Thursday 6 July 2023 with 27 participants consisting of 25 students and 2 boarding school administrators. The results that have been obtained from this activity are that the participants' knowledge about disaster mitigation in Islamic boarding schools has proven to have increased, the skills of Islamic boarding school administrators and students in extinguishing fires using light fire extinguishers have also been achieved.